Fracture risk in patients with type 2 diabetes under different antidiabetic treatment regimens: a retrospective database analysis in primary care - Pscherer S (Dove Medical Press, 2016)
S Pscherer,1 K Kostev,2 FW Dippel,3 W Rathmann4 1Department of Diabetology, Klinikum Traunstein, Kliniken Südostbayern AG, Traunstein, 2Epidemiology Department, IMS Health, Frankfurt, 3Sanofi-Aventis Deutschland GmbH, Berlin, 4German Diabetes Center, Institute for Biometrics and Epidemiology, Leibniz Center for Diabetes Research at Heinrich Heine University, Düsseldorf, Germany Aim: Type 2 diabetes is associated with an increased risk of fractures. There are a few studies on the effects of diabetes treatment on fracture risk. The aim was to investigate the fracture risk related to various types of insulin therapy in primary care practices. Methods: Data from 105,960 type 2 diabetes patients from 1,072 general and internal medicine practices in Germany were retrospectively analyzed (Disease Analyzer database; 01/2000–12/2013). Fracture risk of the following therapies was compared using multivariate logistic regression models adjusting for age, sex, diabetes care, comorbidity, and glycemic control (HbAlc): 1) incident insulin therapy versus oral antidiabetic drugs, 2) basal-supported oral therapy versus supplementary insulin therapy versus conventional insulin therapy, and 3) insulin glargine versus insulin detemir versus NPH insulin. Results: There was a lower odds of having incident fractures in the oral antidiabetic drug group compared to incident insulin users, although not significant (odds ratio [OR]; 95% confidence interval: 0.87; 0.72–1.06). There were increased odds for conventional insulin therapy (OR: 1.59; 95% CI [confidence interval] 0.89–2.84) and supplementary insulin therapy (OR: 1.20; 0.63–2.27) compared to basal-supported oral therapy, which was not significant as well. Overall, there was no significant difference in fracture risk for basal insulins (glargine, detemir, NPH insulin). After a treatment duration ≥2 years, insulin glargine showed a lower odds of having ≥1 fracture compared to NPH users (OR: 0.78; 0.65–0.95) (detemir vs NPH insulin: OR: 1.03; 0.79–1.36). Conclusion: Long-standing therapy with insulin glargine was associated with a lower odds of having any fractures compared to NPH insulin. Further studies are required to investigate whether the lower chance is due to a reduced frequency of hypoglycemia. Keywords: type 2 diabetes, fracture risk, insulin treatment, oral antidiabetic medication, primary care